Conocimiento didáctico matemático en la dimensión epistémica, para la enseñanza del objeto inecuaciones : una perspectiva desde las concepciones y creencias del profesor - Piratoba Gil, Leonardo Marcedonio (Facultad de Ciencias de la Educación, 2024)
Eng: The objective of this study is to characterize the mathematical didactic knowledge in the epistemic and cognitive dimension, for the inaccuracies of the object, according to the conceptions and beliefs of the teacher regarding the global meaning of the mathematical object. Given the importance they have in the Colombian curriculum, it is important to analyze the mathematical content knowledge of teachers, understood as the knowledge they have of the epistemic dimension of mathematical objects, as well as the knowledge acquired in the training process as teachers and fruit of your experience. The theoretical and methodological framework on which the research is based corresponds to the Ontosemiotic Approach to Knowledge and Mathematical Instruction – EOS. The study is established as a descriptive, qualitative research that corresponds to a case study, from which the preliminary analyzes are taken as phases; conception and a priori analysis of didactic situations; experimentation and finally evaluation. The study investigates the experience of 5 mathematics graduate teachers from different sectors of secondary education (public and private). The purpose of the study is to analyze the mathematical didactic knowledge in the epistemic and cognitive dimension according to the development of situations and problems of Inequalities, posed to the teachers who participate in the study.